Humor me : an anthology of funny contemporary writing (plus some great old stuff too) - Frazier, Ian; Keillor, Garrison; Martin, Steve, 1945-; Friedman, Bruce Jay, 1930-; Updike, John; Twain, Mark, 1835-1910 (Ecco, 2010)
"A literary cavalcade ... featuring more than fifty pieces of the greatest comic writing of our time"--Dust jacket.